Transforming power with Pose: Centering love in state-sponsored services for LGBTQ youth experiencing homelessness. Issue 3 (3rd July 2022) - Trochmann, Maren B.; Millesen, Judith L.
Abstract: The disproportionate numbers of LGBTQ youth experiencing homelessness presents moral and ethical dilemmas, carries high emotional and social costs for those without safe, adequate housing, and impacts society at-large. This paper argues that rather than traditional, power-over responses that perpetuate oppression, ostracization, and feelings of powerlessness experienced by young people at multiple intersections of marginalization, public service approaches can foster power-with . The ballroom culture captured in the television series Pose provides critical insight to creating systemic change and justice from a starting point of communal love and power-with . By rejecting the politics of domination in favor of the politics of love, these approaches reaffirm self-efficacy and agency, and ultimately lead toward justice.